2021
DOI: 10.26650/eurjbiol.2021.1023136
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Petroselinum crispum (Parsley) Extract Against Methotrexate-Induced Hepatotoxicity

Abstract: Objective: By inhibiting the synthesis of thymidine and purine, and thereby DNA synthesis, Methotrexate (MTX), suppresses the proliferation of cancer cells. It is thought that the side-effect mechanism is related to oxidant molecules derived from MTX metabolism. In this study, we examined whether the Petroselinum crispum extracts (PCr; parsley) of which the antioxidant properties have been previously shown, was protective against MTX induced liver damage.Materials and Methods: Sprague Dawley rats (female/male;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…While the groups treated with n-BuOH fraction demonstrated a higher significant decrease (P< 0.01) of ALT level from (82.4 ± 2.1 to 41.5 ± 4.7 U/L) when compared with the toxic group, as shown in Figure 2 exhibited the treatment of mice with a high concentration (400 mg/kg) of each extract showed the highest reduction in ALT levels. These findings are in agreement with reported studies [19][20][21] .…”
Section: Alanine-aminotransferase (Alt) Levelsupporting
confidence: 94%
“…While the groups treated with n-BuOH fraction demonstrated a higher significant decrease (P< 0.01) of ALT level from (82.4 ± 2.1 to 41.5 ± 4.7 U/L) when compared with the toxic group, as shown in Figure 2 exhibited the treatment of mice with a high concentration (400 mg/kg) of each extract showed the highest reduction in ALT levels. These findings are in agreement with reported studies [19][20][21] .…”
Section: Alanine-aminotransferase (Alt) Levelsupporting
confidence: 94%
“…These compounds offer several health-promoting benefits like anti-inflammatory actions, cardiovascular health support, and anti-cancer properties. [8] In addition, it has been reported that parsley has antidiabetic effects [9][10][11] and protective effects against hepatotoxicity. [12] Another essential compound in parsley is carnosic acid.…”
Section: Resultsmentioning
confidence: 99%
“…In the present experiment, MTX administration significantly lowered tissue GSH in the induction group when compared to the negative control group. An animal study of Petroselinum crispum hepatoprotective effects in methotrexate-induced liver injury by B. Ertas et al showed comparable results by MTX administration (Ertas et al 2021). Additionally, MTX injection in a study in mice evaluating the hepatoprotective activity of vitamin C, significantly decreased the tissue level of GSH (Mohammed and Al-Gareeb 2021).…”
Section: Discussionmentioning
confidence: 95%